Antarctic and Southern Ocean dust transport pathways: Forward-trajectory modeling and rare earth element source constraints from the RICE ice core - Neff, Peter David (11704814) (2015)
Mineral dust fertilization of Southern Ocean surface waters, and mixing with Antarctic deep-water, influences oceanic uptake of carbon dioxide and draws down global atmospheric concentrations during glacial periods. Quantifying modern variability in dust source and transport strength, especially with respect to high- and low-latitude climate phenomena (e.g. the Southern Annular Mode, El Niño Southern Oscillation), will improve understanding of this important aspect of the global carbon cycle. Using high-order geochemical provenance techniques can also reveal in greater detail what aspects of dust transport are recorded in Antarctic ice core records, allowing for better interpretation of glacial-interglacial dust records at individual sites. First, using forward trajectories and climate reanalysis data, this work explores modern variability (1979-2013) in atmospheric transport of mineral dust from Southern Hemisphere potential source areas (PSA)—primarily Australia, southern South America and southern Africa. Estimates of the relative source and transport strength of New Zealand are also discussed, and compared with other dust PSA to evaluate New Zealand’s potential contribution to Southern Ocean and Antarctic dust deposition. Extra-Antarctic dust PSA distributions are detailed for individual ice core sites, including the newly recovered Roosevelt Island Climate Evolution (RICE) ice core (79.36ºS, 161.71ºW, 550 m a.s.l.). This approach—applicable to many types of aerosol—reveals persistent, strong transport from New Zealand and Patagonia to the southern high-latitudes during all seasons. It also demonstrates that southward transport of air masses from pan-Pacific dust sources is affected by circulation variability initiated in the central tropical Pacific Ocean. High-resolution discrete sampling of the RICE core allows for unprecedented analysis of trace elements at sub-annual to annual scales. The rare earth elements (REE, lanthanide elements Lanthanum to Lutetium) can preserve the signature of their original source material and thus provide provenance constraints for dust preserved in Antarctic snow and ice. While challenging, measurements of REE concentration to the single femtogram per gram (10-15 g g-1) level have been made by combining efficient sample introduction and a jet-interface sector-field inductively coupled plasma mass spectrometer. The methodology and fidelity of these measurements are presented, in addition to results for other low-concentration elements associated with natural and anthropogenic aerosols. REE data from the RICE ice core are then used to explore possible modern sources of dust in the Ross Sea sector of Antarctica, testing hypothesized trajectory model distributions. Twentieth-century and late-Holocene (2.3 ka – present) REE data from the RICE ice core represent the first measurements of this kind from the Pacific sector of Antarctica. RICE data are compared with Holocene REE data from the Drønning Maud Land and Dome C ice cores, with consideration of REE signatures in dust samples from PSA. Data from the RICE ice core indicate fewer than 5% contributions of dust from South America, and show strong negative trends in crustal-normalized REE signatures suggesting contributions from local Antarctic dust.